2019
DOI: 10.1103/physrevd.100.083511
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical system analysis of generalized energy-momentum-squared gravity

Abstract: In this work we have investigated the dynamics of a recent modification to the general theory of relativity, the energy-momentum squared gravity model f (R, T 2 ), where R represents the scalar curvature and T 2 the square of the energy-momentum tensor. By using dynamical system analysis for various types of gravity functions f (R, T 2 ), we have studied the structure of the phase space and the physical implications of the energy-momentum squared coupling. In the first case of functional where f (R, T 2 ) = f0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 83 publications
0
50
0
1
Order By: Relevance
“…For example, in GR the solutions for matter and radiation are ρ m ∼ a −3 and ρ r ∼ a −4 , which tells us that radiation is the dominant component in the early universe where a is very small. In our case, we need to solve equations (17) and (18) simultaneously for matter and radiation content, which can be quite difficult analytically without resorting to some kind of approximation. In appendix B, we show that indeed radiation will be dominant in the early universe in EMSG.…”
Section: A Two-component Fluidsmentioning
confidence: 99%
“…For example, in GR the solutions for matter and radiation are ρ m ∼ a −3 and ρ r ∼ a −4 , which tells us that radiation is the dominant component in the early universe where a is very small. In our case, we need to solve equations (17) and (18) simultaneously for matter and radiation content, which can be quite difficult analytically without resorting to some kind of approximation. In appendix B, we show that indeed radiation will be dominant in the early universe in EMSG.…”
Section: A Two-component Fluidsmentioning
confidence: 99%
“…For instance, η = 0 leads mathematically to exactly the same background dynamics as ΛCDM and η 0 to a wCDM-type cosmological model, despite the only physical source in the model being dust [46]. A recent study constraining the model from the low-redshift cosmological data can be found in [53] and a dynamical systems analysis in [54]. EMPG results in both u(z) and v(z) arising dynamically and could be investigated for producing effective DE passage below zero at large redshifts.…”
Section: Introductionmentioning
confidence: 97%
“…Morares and Sahoo [17] studied nonexotic matter wormholes while Akarsu [18] explored possible constraints from neutron stars in the same frame. Bahamonde et al [19] investigated the minimal and nonminimal coupling models of EMSG and observed that these models describe the current cosmic accelerated expansion. ere has been a recent literature [20][21][22] that indicates various cosmological applications of this modified theory.…”
Section: Introductionmentioning
confidence: 99%
“…Since EMSG is established to overcome the singularities, it is significant to analyze the inner region of massive objects where energy factor is quite strong to see the deviations of EMSG from GR. In this paper, we formulate Noether symmetry generators and corresponding conserved quantities for a minimal coupling model of EMSG, i.e., f(R, T 2 ) � αR n + β(T 2 ) m , n, m ≠ 0, 1, and α, β ≠ 0 [19]. We then discuss some salient features of compact objects such as effective matter variables, energy conditions, compactness parameter, gravitational redshift, stability against equilibrium forces, and sound speed for particular values of the model parameters.…”
Section: Introductionmentioning
confidence: 99%